Nonlinear dynamic characteristics of horizontal-axis wind turbine blades including pre-twist. (15th July 2022) - Jokar, H.; Mahzoon, M.; Vatankhah, R.
Abstract: This paper focuses on the dynamic modeling and vibration analysis of horizontal axis wind turbine (HAWT) blades with emphasis on the effects of the pre-twist, rotational rigid body motion and coupling among the different blade's degrees of freedom. The blade is considered as a rotating pre-twisted beam mounted on a rigid hub with a constant angle relative to the plane of rotation, so-called precone angle. Kinetic energy of the blade based on its elastic as well as rigid motion together with its strain energy and generalized forces resulting from gravitational, centrifugal and aerodynamic loadings are obtained and used to derive new coupled dynamic equations by means of Hamilton's principle. The weak formulation is constructed and the Rayleigh-Ritz method (RRM) is adopted to extract a reduced order model (ROM) for the blade's vibration analysis. The developed nonlinear ROM is linearized around the steady-state solution and the blade's dynamic characteristics are obtained. The reference wind turbine blade called NREL 5-MW HAWT blade is selected as the case-study and effects of pre-twist, centrifugal force, angular velocity-depended terms, nonlinearities and transverse static loads on its dynamic characteristics are investigated. Results are shown to be in good agreement with available data in the literature. Highlights: A new nonlinear formulation is developed for vibration of horizontal axis wind turbine blades. The coupling among the different modes and the pre-twist effects are included. A modified BEM theory is presented for calculation of Aerodynamic loads. Contributions of the terms on the blade dynamic characteristics are investigated. The reference wind turbine blade called NREL 5-MW HAWT blade is selected as the case-study.